International or national implementers—Who is better? Evidence from a framing experiment - Lennart C. Kaplan; Jana Kuhnt; Katharina Richert (Review of Development Economics, 2023)
Behavioral economics has shown that changing small features in framing a context or action may drastically change behavior. A key factor characterizing most development interventions is the salience of either a local or an international implementer. Using the setup of an intervention conducted in Indonesia, we show that the study population in the Acehnese context exhibits higher levels of support for the project if the participation of international actors is highlighted. We find that previous experience with the respective actor is pivotal. Qualitative evidence suggests that internationals' perceived skills drive results, highlighting the importance of strengthened local capacities for positive experiences with local implementers. Overall, the study underlines the benefits of linking framing experiments to the actual experiences of respondents to generate insights into the real world.
Keywords: 330; behavioral economics; framing experiment; public health